2013
DOI: 10.2196/jmir.2565
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming Addictions, a Web-Based Application, and SMART Recovery, an Online and In-Person Mutual Help Group for Problem Drinkers, Part 1: Three-Month Outcomes of a Randomized Controlled Trial

Abstract: BackgroundOvercoming Addictions (OA) is an abstinence-oriented, cognitive behavioral, Web application based on the program of SMART Recovery. SMART Recovery is an organization that has adapted empirically supported treatment strategies for use in a mutual help framework with in-person meetings, online meetings, a forum, and other resources.ObjectiveTo evaluate the effectiveness of OA and SMART Recovery (SR) with problem drinkers who were new to SMART Recovery. Our experimental hypotheses were: (1) all groups w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
110
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(119 citation statements)
references
References 28 publications
7
110
1
1
Order By: Relevance
“…In a subsequent study conducted entirely over the internet, Campbell, Hester and colleagues compared a cognitive-behavioral online program with components of MI called Overcoming Addictions in combination with an online and in-person mutual help group for problem drinkers called SMART Recovery (SR) (OA+SR) to SMART Recovery alone (Campbell, Hester, Lenberg, & Delaney, 2016; Hester, Lenberg, Campbell, & Delaney, 2013) in 189 heavy drinkers (AUDIT mean 24.7). Three and six-month follow-up indicated significant reductions in drinking outcomes, but no significant differences between conditions (PDA at 3 months follow up was 73.3 for OA+SR compared with 71.2 for SR only).…”
Section: The Promise Of Technologymentioning
confidence: 99%
“…In a subsequent study conducted entirely over the internet, Campbell, Hester and colleagues compared a cognitive-behavioral online program with components of MI called Overcoming Addictions in combination with an online and in-person mutual help group for problem drinkers called SMART Recovery (SR) (OA+SR) to SMART Recovery alone (Campbell, Hester, Lenberg, & Delaney, 2016; Hester, Lenberg, Campbell, & Delaney, 2013) in 189 heavy drinkers (AUDIT mean 24.7). Three and six-month follow-up indicated significant reductions in drinking outcomes, but no significant differences between conditions (PDA at 3 months follow up was 73.3 for OA+SR compared with 71.2 for SR only).…”
Section: The Promise Of Technologymentioning
confidence: 99%
“…Results indicated that individuals in SMART Recovery demonstrated more of an internal locus of control and less dependence on a higher power when it came to regulating drinking (or drug)-related behaviors compared with 12-step members. Hester, Lenberg, Campbell, and Delaney (2013) found that individuals who attended SMART Recovery meetings, and Overcoming Addictions (a web application based on the SMART Recovery program), demonstrated an increase in percentage of days abstinent, reduction in substance related issues, and a reduction in drinks per drinking day. Penn and Brooks (2000) mentioned no statistically significant differences in outcome for 12-step and SMART Recovery participants on the Addiction Severity Index Scale (ASI), alcohol, drug, psychiatric, legal, and employment composites, though statistical data were not reported.…”
Section: Smart Recovery: Principles Philosophy and Mechanisms For Cmentioning
confidence: 99%
“…However, both were very small (with N’s=20 and 70), and conclusions are strictly limited by the fact that these studies tested not involvement in mutual help alternatives per se , but rather interventions informed by their theoretical principles. Finally, one longitudinal randomized trial testing the efficacy of a web-based intervention drawing on SMART principles (i.e., Overcoming Addictions) has, as a part of the analysis, examined associations between SMART in-person attendance and alcohol outcomes over time (Hester, Lenberg, Campbell, & Delaney, 2013). Participants for this study were randomized to SMART in-person meetings only (SMART Only), Overcoming Addictions Only, or SMART Plus Overcoming Addictions.…”
Section: Introductionmentioning
confidence: 99%